TAFSIR TARBAW?: WACANA KHALIFAH DAN KHIL?FAH DALAM REFORMASI PENDIDIKAN ISLAM HOLISTIK - Abd Aziz; Fatkhul Mubin (Universitas PTIQ Jakarta, 2021)
This study is intended to describe the discourse of the caliphate and caliphate in the reform of holistic Islamic education through holistic education. The goal of holistic Islamic education reform is to produce a generation of caliphs with the political thought of the caliphate as caliphs as individuals and groups who have the potential to fight for and realize